Two-component organic silicon heat-conducting wave-absorbing gel and preparation method thereof
By using a two-component silicone thermally absorbing gel in a thermally conductive silicon gel, the polymerization and cross-linking of vinyl-terminated polysiloxane and vinyl silicone oil with modified fillers is used to combine the packaging of polyaniline compounds. The covering technology solves the problems of low thermal conductivity and insufficient electromagnetic radiation absorption capacity of thermal silicon gels, and achieves efficient thermal conductivity and electromagnetic wave absorption effects.
Patent Information
- Application Number
- CN202411565971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic silicon gel, in particular to a two-component organic silicon thermal conductive wave absorbing gel and a preparation method thereof. Background Art
[0002] Semiconductors such as computers (CPLs), transistors, and light-emitting diodes (LEDs) generate heat during use, and the heat sometimes causes the performance of electronic components to decline. Therefore, a heat sink is installed on the electronic components that generate heat. However, since the heat sink is mostly made of metal, the electronic components and the heat sink cannot fit well. Therefore, a gel is used to improve the adhesion between the heat sink and the substrate.
[0003] The thermal conductivity of traditional thermally conductive silicone gel is low, and the performance of electronic devices has improved dramatically in recent years, and the heat generation has also increased. Therefore, the thermal conductivity requirements for thermally conductive polymer compositions are getting higher and higher. The existing technology improves the thermal conductivity of thermally conductive polymers by increasing the content of thermally conductive inorganic powders such as alumina (such as alumina). However, simply adding thermally conductive inorganic powders has poor dispersion inside the gel, which affects the original thermal conductivity. In addition, with the development of science and technology, daily life is inseparable from electronic products. At the same time, excessive electromagnetic radiation will also bring a series of problems such as electromagnetic pollution and electromagnetic interference. In a complex electromagnetic environment, in order to ensure the normal operation of electronic components, it is necessary to absorb or shield the electromagnetic waves to a certain extent. Therefore, there is an urgent need for a silicone gel material with wave absorption and thermal conductivity to meet the functional diversification needs of electronic components. Summary of the invention
[0004] The purpose of the present invention is to provide a two-component organic silicon thermal conductive wave absorbing gel and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a two-component silicone thermal conductive wave absorbing gel, comprising component A, component B and modified filler, calculated by weight:
[0006] Component A:
[0007] 30-50 parts of vinyl-terminated polysiloxane;
[0008] 0.1 to 2 parts of tackifier;
[0009] Component B:
[0010] 30-50 parts of vinyl silicone oil;
[0011] 0.4-2 parts of catalyst;
[0012] 0.1 to 1 part of antioxidant.
[0013] Furthermore, the preparation method of the two-component silicone thermal conductive and wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:0.8-1.2:0.5-1, and stirred for reaction at a vacuum degree of 0.06-0.095 MPa, a rotation speed of 300-800 rpm and 80° C. for 0.5-1 h.
[0014] Furthermore, the vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity ranging from 100 to 10000 mPa·s.
[0015] Furthermore, the viscosity of the vinyl-terminated polysiloxane is 100 to 5000 cps.
[0016] Furthermore, the catalyst is a titanium complex catalyst.
[0017] Furthermore, the tackifier is vinyltrimethoxysilane.
[0018] Furthermore, the antioxidant is any one or a combination of at least two of tris(2,4-di-tert-butylphenyl)phosphite, dinonyldiphenylamine or 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid.
[0019] Furthermore, the preparation method of the modified filler is as follows:
[0020] (1) washing the graphite with anhydrous ethanol, acetone, and deionized water, and drying the graphite sheet after washing;
[0021] (2) The graphite obtained in step (1) and boric anhydride are fully mixed in a mass ratio of 1:0.01 to 0.1, and the mixture is placed in a graphite crucible, which is then placed in a chemical vapor deposition reactor and evacuated to 10 -5 ~10 -4 Pa, the temperature is raised to 1500-1530°C at 8-14°C / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle at a flow rate of 18-27L / min, and argon enters the reaction chamber through the lower nozzle at a flow rate of 12-18L / min. After reacting for 10-15min, the temperature is raised to 1600-1620°C, silicon tetrachloride enters the reaction chamber through the upper nozzle at a flow rate of 6-11L / min, and the reaction is continued for 15min, then the gas is stopped and the furnace is cooled to room temperature. The obtained mixture is kept at 50°C for 8h in air and at 900°C for 1h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric hot air drying oven for 24h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas, with a flow rate of 25-35L / min;
[0022] (3) 4-12 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.1-0.4 g of 4-anilinotriethoxysilane was added, and the mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and filtered, and washed with deionized water for 6-8 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 0.5-20%;
[0023] (4) Add aniline to the suspension obtained in step (3) until the aniline concentration is 0.05-0.4 mol / L, adjust the pH to 1-4 with hydrochloric acid, stir at 60 rpm for 1-3 h, add ferric nitrate, the molar ratio of ferric nitrate to aniline is 2:1-1:2, continue stirring at 0-4°C for 2-4 h, then add 2-allylaniline, the molar ratio of 2-allylaniline to aniline is 0.5:1, continue stirring for 12 h, centrifuge and filter the filtrate, wash with deionized water for 6-8 times, and dry at 60°C to constant weight.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0025] The present invention adopts graphite as a carbon source and boric anhydride as a catalyst to prepare a beaded silicon carbide powder. The present invention performs impurity removal treatment on graphite in advance to avoid interference of impurity elements on the performance of silicon carbide, then SiH4 gas provides a silicon source to preliminarily form a silicon carbide seed, then silicon tetrachloride is introduced to dope the silicon source, a gas phase substance containing Cl-Si bonds is introduced, gas phase silicon is promoted to transform into a solid state, thereby accelerating the growth rate, and avoiding premature nucleation growth, so that the gas supersaturation is increased, and at the same time, the ambient temperature is controlled, epitaxy is deposited on the surface of the seed, and a beaded structure is finally formed, which effectively increases the specific surface area of the filler, helps to improve its interface polarization loss, and thus strengthens the wave absorption effect of the gel, and the structure size is different, so it is easier to build a network structure in the gel, improve the thermal conductivity and wave absorption performance of the gel, and then a polyaniline compound containing multiple unsaturated bonds is coated on the surface of the filler to improve its high conductivity and enhance the electromagnetic wave absorption performance of the gel.
[0026] The organic silicone gel used in the present invention has component A with vinyl-terminated polysiloxane as the main raw material, and component B with vinyl silicone oil as the main raw material. During high-speed mixing under vacuum conditions, the main raw materials of each component and the filler are polymerized, cross-linked and solidified, and further assembled to form a three-dimensional network structure to obtain the final organic silicone gel. The filler is assembled and coated with a polyaniline compound, and is more likely to form a heat-conducting and wave-absorbing channel when dispersed in a matrix. It can also effectively reduce phonon scattering, extend the electron transmission path, and further enhance its conductivity loss, thereby effectively improving the thermal conductivity and wave-absorbing performance of the gel. The high-speed mixing eliminates tiny pores inside the gel, thereby further reducing the contact thermal resistance between the components inside the gel and improving its thermal conductivity. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are provided in detail. The test methods for various indicators of the gel prepared in the following examples are as follows:
[0029] The thermal conductivity of the material was measured according to ASTMD5470;
[0030] The electromagnetic parameters of the material in the frequency range of 2 to 18 GHz were measured on a vector network analyzer.
[0031] Example 1
[0032] A two-component organic silicon thermal conductive wave absorbing gel, comprising component A, component B and modified filler, calculated by weight:
[0033] Component A:
[0034] 30 parts of vinyl terminated polysiloxane;
[0035] 0.1 part of vinyltrimethoxysilane;
[0036] Component B:
[0037] 30 parts of vinyl silicone oil;
[0038] 0.4 parts of titanium complex catalyst;
[0039] 0.1 part of tris(2,4-di-tert-butylphenyl) phosphite;
[0040] The preparation method of the two-component organic silicon thermal conductive wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:0.8:0.5, and stirred for reaction at a vacuum degree of 0.08 MPa, a rotation speed of 800 rpm and 80° C. for 1 hour;
[0041] The preparation method of the modified filler is as follows:
[0042] (1) washing the graphite with anhydrous ethanol, acetone, and deionized water, and drying the graphite sheet after washing;
[0043] (2) The graphite obtained in step (1) and boric anhydride were fully mixed in a mass ratio of 1:0.1, loaded into a graphite crucible, and then placed in a chemical vapor deposition reactor, and evacuated to 10 -5 Pa, the temperature is raised to 1530℃ at 10℃ / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle with a flow rate of 25L / min, and argon enters the reaction chamber through the lower nozzle with a flow rate of 12L / min. After reacting for 15 minutes, the temperature is raised to 1620℃, and silicon tetrachloride enters the reaction chamber through the upper nozzle with a flow rate of 6L / min. After continuing to react for 15 minutes, the gas is stopped and cooled to room temperature with the furnace. The obtained mixture is kept at 50℃ in air for 8h and 900℃ for 1h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric hot air drying oven for 24h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas, with a flow rate of 35L / min;
[0044] (3) 5 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.2 g of 4-anilinotriethoxysilane was added. The mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and washed with deionized water for 7 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 5%;
[0045] (4) Aniline was added to the suspension obtained in step (3) until the concentration of aniline was 0.1 mol / L, and then the pH was adjusted to 1 with hydrochloric acid. After stirring at 60 rpm for 2 h, ferric nitrate was added in a molar ratio of ferric nitrate to aniline of 1:1. Stirring was continued at 0°C for 3 h, and then 2-allylaniline was added in a molar ratio of 2-allylaniline to aniline of 0.5:1. Stirring was continued for 12 h. The filtrate was collected by centrifugation, washed 7 times with deionized water, and dried at 60°C to constant weight.
[0046] Example 2
[0047] A two-component organic silicon thermal conductive wave absorbing gel, comprising component A, component B and modified filler, calculated by weight:
[0048] Component A:
[0049] 36 parts of vinyl terminated polysiloxane;
[0050] 0.2 parts of vinyltrimethoxysilane;
[0051] Component B:
[0052] 36 parts of vinyl silicone oil;
[0053] 0.6 parts of titanium complex catalyst;
[0054] 0.1 part of tris(2,4-di-tert-butylphenyl) phosphite;
[0055] The preparation method of the two-component organic silicon thermal conductive wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:0.9:0.5, and stirred for reaction at a vacuum degree of 0.08 MPa, a rotation speed of 800 rpm and 80° C. for 1 hour;
[0056] The preparation method of the modified filler is as follows:
[0057] (1) washing the graphite with anhydrous ethanol, acetone, and deionized water, and drying the graphite sheet after washing;
[0058] (2) The graphite obtained in step (1) and boric anhydride were fully mixed in a mass ratio of 1:0.1, loaded into a graphite crucible, and then placed in a chemical vapor deposition reactor, and evacuated to 10 -5 Pa, the temperature is raised to 1530℃ at 10℃ / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle with a flow rate of 25L / min, and argon enters the reaction chamber through the lower nozzle with a flow rate of 12L / min. After reacting for 15 minutes, the temperature is raised to 1620℃, and silicon tetrachloride enters the reaction chamber through the upper nozzle with a flow rate of 6L / min. After continuing to react for 15 minutes, the gas is stopped and cooled to room temperature with the furnace. The obtained mixture is kept at 50℃ in air for 8h and 900℃ for 1h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric hot air drying oven for 24h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas, with a flow rate of 35L / min;
[0059] (3) 5 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.1 g of 4-anilinotriethoxysilane was added. The mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and washed with deionized water for 7 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 10%;
[0060] (4) Aniline was added to the suspension obtained in step (3) until the concentration of aniline was 0.2 mol / L, and then the pH was adjusted to 1 with hydrochloric acid. After stirring at 60 rpm for 2 h, ferric nitrate was added in a molar ratio of ferric nitrate to aniline of 1:1. Stirring was continued at 0°C for 3 h, and then 2-allylaniline was added in a molar ratio of 2-allylaniline to aniline of 0.5:1. Stirring was continued for 12 h. The filtrate was collected by centrifugation, washed 7 times with deionized water, and dried at 60°C to constant weight.
[0061] Example 3
[0062] A two-component organic silicon thermal conductive wave absorbing gel, comprising component A, component B and modified filler, calculated by weight:
[0063] Component A:
[0064] 43 parts of vinyl terminated polysiloxane;
[0065] 1 part of vinyltrimethoxysilane;
[0066] Component B:
[0067] 43 parts of vinyl silicone oil;
[0068] 1 part of titanium complex catalyst;
[0069] 0.5 parts of dinonyldiphenylamine;
[0070] The preparation method of the two-component organic silicon thermal conductive wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:1:0.7, and stirred for reaction at a vacuum degree of 0.08 MPa, a rotation speed of 800 rpm and 80° C. for 1 hour;
[0071] The preparation method of the modified filler is as follows:
[0072] (1) washing the graphite with anhydrous ethanol, acetone, and deionized water, and drying the graphite sheet after washing;
[0073] (2) The graphite obtained in step (1) and boric anhydride were fully mixed in a mass ratio of 1:0.1, loaded into a graphite crucible, and then placed in a chemical vapor deposition reactor, and evacuated to 10 -5 Pa, the temperature is raised to 1530℃ at 10℃ / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle with a flow rate of 25L / min, and argon enters the reaction chamber through the lower nozzle with a flow rate of 12L / min. After reacting for 15 minutes, the temperature is raised to 1620℃, and silicon tetrachloride enters the reaction chamber through the upper nozzle with a flow rate of 6L / min. After continuing to react for 15 minutes, the gas is stopped and cooled to room temperature with the furnace. The obtained mixture is kept at 50℃ in air for 8h and 900℃ for 1h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric hot air drying oven for 24h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas, with a flow rate of 35L / min;
[0074] (3) 10 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.2 g of 4-anilinotriethoxysilane was added. The mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and washed with deionized water for 7 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 10%;
[0075] (4) Aniline was added to the suspension obtained in step (3) until the concentration of aniline was 0.3 mol / L, and then the pH was adjusted to 3 with hydrochloric acid. After stirring at 60 rpm for 2 h, ferric nitrate was added in a molar ratio of ferric nitrate to aniline of 1:1. Stirring was continued at 0°C for 3 h, and then 2-allylaniline was added in a molar ratio of 2-allylaniline to aniline of 0.5:1. Stirring was continued for 12 h. The filtrate was collected by centrifugation, washed 7 times with deionized water, and dried at 60°C to constant weight.
[0076] Example 4
[0077] A two-component organic silicon thermal conductive wave absorbing gel, comprising component A, component B and modified filler, calculated by weight:
[0078] Component A:
[0079] 50 parts of vinyl terminated polysiloxane;
[0080] 2 parts of vinyltrimethoxysilane;
[0081] Component B:
[0082] 50 parts of vinyl silicone oil;
[0083] 2 parts of titanium complex catalyst;
[0084] 1 part of dinonyldiphenylamine;
[0085] The preparation method of the two-component organic silicon thermal conductive wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:1.2:1, and stirred for reaction at a vacuum degree of 0.08 MPa, a rotation speed of 800 rpm and 80° C. for 1 hour;
[0086] The preparation method of the modified filler is as follows:
[0087] (1) washing the graphite with anhydrous ethanol, acetone, and deionized water, and drying the graphite sheet after washing;
[0088] (2) The graphite obtained in step (1) and boric anhydride were fully mixed in a mass ratio of 1:0.1, loaded into a graphite crucible, and then placed in a chemical vapor deposition reactor, and evacuated to 10 -5Pa, the temperature is raised to 1530℃ at 10℃ / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle with a flow rate of 25L / min, and argon enters the reaction chamber through the lower nozzle with a flow rate of 12L / min. After reacting for 15 minutes, the temperature is raised to 1620℃, and silicon tetrachloride enters the reaction chamber through the upper nozzle with a flow rate of 6L / min. After continuing to react for 15 minutes, the gas is stopped and cooled to room temperature with the furnace. The obtained mixture is kept at 50℃ in air for 8h and 900℃ for 1h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric hot air drying oven for 24h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas, with a flow rate of 35L / min;
[0089] (3) 12 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.4 g of 4-anilinotriethoxysilane was added. The mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and washed with deionized water for 7 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 15%;
[0090] (4) Aniline was added to the suspension obtained in step (3) until the concentration of aniline was 0.4 mol / L, and then the pH was adjusted to 1 with hydrochloric acid. After stirring at 60 rpm for 2 h, ferric nitrate was added in a molar ratio of ferric nitrate to aniline of 1:1. Stirring was continued at 0°C for 3 h, and then 2-allylaniline was added in a molar ratio of 2-allylaniline to aniline of 0.5:1. Stirring was continued for 12 h. The filtrate was collected by centrifugation, washed 7 times with deionized water, and dried at 60°C to constant weight.
[0091] Comparative Example 1
[0092] The difference between Comparative Example 1 and Example 4 is that vacuum high-speed stirring is not performed during the preparation of the two-component organic silicone thermally conductive and wave-absorbing gel, and the remaining steps are the same as those of Example 4.
[0093] Comparative Example 2
[0094] The difference between Comparative Example 2 and Example 4 is that silicon tetrachloride is not introduced during the preparation of the modified filler, and the remaining steps are the same as Example 4.
[0095] Comparative Example 3
[0096] The difference between Comparative Example 3 and Example 4 is that 2-allylaniline is not added during the preparation of the modified filler, and the remaining steps are the same as Example 4.
[0097] Comparative Example 4
[0098] The difference between Comparative Example 4 and Example 4 is that the beaded silicon carbide is not coated with the polyaniline compound, and the remaining steps are the same as Example 4.
[0099] Effect example
[0100] Table 1 below shows the performance analysis results of the gels of Examples 1 to 4 of the present invention and Comparative Examples 1 to 4.
[0101] Table 1
[0102] Thermal conductivity (W / mK) Reflection loss(dB) Example 1 7.5 -35 Example 2 8.8 -40 Example 3 9.5 -48 Example 4 10.6 -55 Comparative Example 1 8.8 -40 Comparative Example 2 10.0 -30 Comparative Example 3 8.0 -38 Comparative Example 4 7.8 -25
[0103] From the comparison of the experimental data of Examples 1-4 with Comparative Example 1, it can be found that without vacuum high-speed stirring, there are trace bubbles inside the gel, resulting in poor contact performance between internal components, affecting thermal conductivity and reflection loss; from the comparison of the experimental data of Examples 1-4 with Comparative Example 2, it can be found that without the introduction of silicon tetrachloride, the morphology of silicon carbide is affected, the specific surface area is reduced, and the wave absorption performance of the gel is affected; from the comparison of the experimental data of Examples 1-4 with Comparative Example 3, it can be found that without the addition of 2-allylaniline, the binding ability of the filler to the gel is weakened, and its dispersibility inside the gel is affected, thereby affecting the thermal conductivity and reflection loss value of the gel; from the comparison of the experimental data of Examples 1-4 with Comparative Example 4, it can be found that without polyaniline treatment of silicon carbide, the electrical conductivity is reduced, the electromagnetic wave absorption of the gel is affected, and it cannot participate in the polymerization and cross-linking between components, and a network channel cannot be constructed.
[0104] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A two-component silicone thermally conductive and wave-absorbing gel, comprising component A, component B and a modified filler, characterized in that: By weight: Component A: 30-50 parts of vinyl terminated polysiloxane; Thickener 0.1~2 parts; Component B: 30-50 parts of vinyl silicone oil; Catalyst 0.4~2 parts; Antioxidant 0.1~1 part.
2. A two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The preparation method of the two-component organic silicon thermal conductive wave absorbing gel is as follows: component A, component B and modified filler are mixed in a weight ratio of 1:0.8-1.2:0.5-1, and stirred for reaction at a vacuum degree of 0.06-0.095 MPa, a rotation speed of 300-800 rpm and 80° C. for 0.5-1 h.
3. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity ranging from 100 to 10000 mPa·s.
4. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The viscosity of the vinyl terminated polysiloxane is 100-5000 cps.
5. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The catalyst is a titanium complex catalyst.
6. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The tackifier is vinyltrimethoxysilane.
7. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The antioxidant is any one or a combination of at least two of tris(2,4-di-tert-butylphenyl)phosphite, dinonyldiphenylamine or 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid.
8. The two-component silicone thermally conductive and wave-absorbing gel according to claim 1, characterized in that: The preparation method of the modified filler is as follows: (1) washing the graphite with anhydrous ethanol, acetone and deionized water, and drying the graphite sheet after washing; (2) The graphite obtained in step (1) and boric anhydride are fully mixed in a mass ratio of 1:0.01-0.1, and loaded into a graphite crucible, which is then placed in a chemical vapor deposition reactor and evacuated to 10 -5 ~10 -4 Pa, the temperature is raised to 1500-1530°C at 8-14°C / min, the gas nozzles of the chemical vapor deposition reactor are divided into three parts: upper, middle and lower. SiH4 enters the reaction chamber through the upper nozzle at a flow rate of 18-27L / min, and argon enters the reaction chamber through the lower nozzle at a flow rate of 12-18L / min. After reacting for 10-15min, the temperature is raised to 1600-1620°C, silicon tetrachloride enters the reaction chamber through the upper nozzle at a flow rate of 6-11L / min, and the reaction is continued for 15min, then the gas is stopped and the furnace is cooled to room temperature. The obtained mixture is kept at 50°C for 8 h in air and at 900°C for 1 h to remove residual carbon. After removing residual SiO2 by immersion in HF acid, it is repeatedly washed with deionized water until neutral, and dried in an electric blast drying oven for 24 h to obtain beaded silicon carbide; the upper and lower nozzles both use hydrogen as carrier gas and dilution gas at a flow rate of 25-35L / min; (3) 4-12 g of beaded silicon carbide and 100 mL of ethanol / water with a volume ratio of 98:2 were stirred at 100 rpm for 30 min, and then 0.1-0.4 g of 4-anilinotriethoxysilane was added. The mixture was stirred and reacted at 60° C. for 12 h. The filtrate was centrifuged and filtered, washed with deionized water for 6-8 times, and then stirred and dispersed in water to prepare a suspension with a weight content of 0.5-20%; (4) Aniline is added to the suspension obtained in step (3) until the concentration of aniline is 0.05-0.4 mol / L, and then the pH is adjusted to 1-4 with hydrochloric acid. After stirring at 60 rpm for 1-3 h, ferric nitrate is added, and the molar ratio of ferric nitrate to aniline is 2:1-1:
2. Stirring is continued at 0-4°C for 2-4 h, and then 2-allylaniline is added, and the molar ratio of 2-allylaniline to aniline is 0.5:
1. Stirring is continued for 12 h, and the filtrate is collected by centrifugation, washed with deionized water for 6-8 times, and dried at 60°C to constant weight.